Osteal and extraosteal effects of vitamin D and its opportunities of medication correction of its deficiency - V. V. Salukhov; E. A. Kovalevskaya; V. V. Kurbanova (Медицинский совет, 2018)
A well-known crucial role of Vitamin D is in the maintenance of musculoskeletal system. In terms of high prevalence of violations of calcium-phosphorus metabolism, in the following article we will touch upon some aspects bone metabolic dysfunction, caused by Vitamin D deficiency. Moreover, recent researches reveal that the great amount of Vitamin D and their importance lead us to calling it a global regulator of homeostasis of human body, so below we are to analyze and generalize the pleiotropic effects of Vitamin D, concerning its influence on organs and systems of organs. Also in this article we bring up the results of some researches, which have persuasively demonstrated that the optimal level of Vitamin D in blood has a positive effects on a humans health and protects it from many more diseases of civilization. Futhermore, there are going to be regarded various methods for medication correction of vitamin D deficiency, and one clinical case of an inadequate diagnosis and treatment of hypovitaminosis D.